2007
DOI: 10.1016/j.ultrasmedbio.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral Transfection of Suspension Cells in Ultrasound Standing Wave Fields

Abstract: Ultrasound-induced cavitation has been widely used for delivering DNA vectors into cells. However, this approach may seriously disrupt cell membranes and cause lethal damage when cells are exposed to the inertial cavitation field. In this study, instead of using sonoporation, ultrasound standing wave fields (USWF) were explored for nonviral transfection of suspension cells. Acoustic resonance in a tubular chamber was generated from the interference of waves emitted from a piezoelectric transducer and consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…An aqueous stock solution of PEI was prepared by diluting 1 mg of the commercial solution in 1000 mL DI water, neutralized with HCl and filtered at 0.2 μm (Millipore, USA). The PEI/DNA complexes were performed by mixing PEI and plasmid DNA at 6:1 of N/P ratio (PEI nitrogen: DNA phosphate ratio) in the DI water [7] . The complexes were incubated for 20-30 min at room temperature and stored in 4°C.…”
Section: Preparation Of Pei/dna Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…An aqueous stock solution of PEI was prepared by diluting 1 mg of the commercial solution in 1000 mL DI water, neutralized with HCl and filtered at 0.2 μm (Millipore, USA). The PEI/DNA complexes were performed by mixing PEI and plasmid DNA at 6:1 of N/P ratio (PEI nitrogen: DNA phosphate ratio) in the DI water [7] . The complexes were incubated for 20-30 min at room temperature and stored in 4°C.…”
Section: Preparation Of Pei/dna Complexesmentioning
confidence: 99%
“…Recent studies have shown that ultrasound-targeted microbubble destruction (UTMD) is a new, non-viral, promising method for the gene delivery to the heart [1][2][3][4][5] . The combination of ultrasound (US) irradiation with polyethylenimine (PEI) can not only improve the transfection efficiency markedly [6,7] , but also achieve specific targeting [8] . Researches showed that UTMD combined with PEI could enhance the transfecZhiyi CHEN, male, born in 1975, Doctorial Candidate E-mai: winchen@smail.hust.edu.cn # Corresponding author * The project was supported by a grant from the National Natural Sciences Foundation of China (No.…”
mentioning
confidence: 99%
“…Effect of NLS peptide and PEI on DNA integrity using a deoxyribonuclease (DNase) protection assay. To determine whether the PEI/NLS complexes protect the pEGFP-N 3 plasmid from DNase degradation reference earlier works (24) in the present study, the pEGFP-N 3 plasmid was incubated with the PEI at N:P ratios of 6:1 (19) with or without 120 µg NLS (24) for 1 h at room temperature. DNase endonuclease (0.25 U; Thermo Fisher Scientific, Inc.) was then added to pEGFP-N3 plasmid, PEI/DNA and PEI/DNA/NLS solutions for 5, 10 or 15 min at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated that UTMD significantly increases the permeability of a cell membrane, thereby improving the efficiency of gene transfection (15)(16)(17). In addition, the combination of ultrasound (US) irradiation with PEI markedly improves transfection efficiency (18,19) and specific targeting (20). Yoo and Jeong (21) demonstrated the plasmid DNA/PEI complexes containing NLS attached to psoralen, a nucleic acid-intercalating agent, increased transfection efficiencies in COS-1 cells, indicating that this complex may be used as a potential DNA carrier for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies use a standing wave field, specifically with planar resonators. Although the mechanisms are unclear, there is evidence to suggest that these systems have the potential to 15 produce high transfection rates and improve viability over that reported using inertial cavitation [75][76][77] . Whilst the potential for poration in planar resonators is promising 78 there still remains little evidence of the cell physiology, cell dynamics, acoustic environment and poration mechanism in such systems.…”
Section: Cell-interaction Studies and Sonoporationmentioning
confidence: 99%